An extreme value model for maximum wave heights based on weather types. Issue 2 (12th February 2016) - Rueda, Ana; Camus, Paula; Méndez, Fernando J.; Tomás, Antonio; Luceño, Alberto
Abstract: Extreme wave heights are climate‐related events. Therefore, special attention should be given to the large‐scale weather patterns responsible for wave generation in order to properly understand wave climate variability. We propose a classification of weather patterns to statistically downscale daily significant wave height maxima to a local area of interest. The time‐dependent statistical model obtained here is based on the convolution of the stationary extreme value model associated to each weather type. The interdaily dependence is treated by a climate‐related extremal index. The model's ability to reproduce different time scales (daily, seasonal, and interannual) is presented by means of its application to three locations in the North Atlantic: Mayo (Ireland), La Palma Island, and Coruña (Spain). Key Points: Weather patterns classification is used to assess extreme wave climate variability Climate‐emulator of extreme events